Thermally drawn fibers as nerve guidance scaffolds. (March 2016) - Koppes, Ryan A.; Park, Seongjun; Hood, Tiffany; Jia, Xiaoting; Abdolrahim Poorheravi, Negin; Achyuta, Anilkumar Harapanahalli; Fink, Yoel; Anikeeva, Polina
Abstract: Synthetic neural scaffolds hold promise to eventually replace nerve autografts for tissue repair following peripheral nerve injury. Despite substantial evidence for the influence of scaffold geometry and dimensions on the rate of axonal growth, systematic evaluation of these parameters remains a challenge due to limitations in materials processing. We have employed fiber drawing to engineer a wide spectrum of polymer-based neural scaffolds with varied geometries and core sizes. Using isolated whole dorsal root ganglia as an in vitro model system we have identified key features enhancing nerve growth within these fiber scaffolds. Our approach enabled straightforward integration of microscopic topography at the scale of nerve fascicles within the scaffold cores, which led to accelerated Schwann cell migration, as well as neurite growth and alignment. Our findings indicate that fiber drawing provides a scalable and versatile strategy for producing nerve guidance channels capable of controlling direction and accelerating the rate of axonal growth.